The potential of legume tree prunings as organic matters for improving phosphorus availability in an acid soil - I Wahyudi; E Handayanto (Brawijaya University, 2015)
A study that was aimed to elucidate roles of Gliricidia sepium and Tithonia diversifolia prunings and their extracted humic and fulvic acids on improving phosphorus availability and decreasing aluminum concentration in an Ultisol was conducted in a glasshouse. Thirteen treatments consisting of two prunings, six rates of pruning application (5, 7.5, 10, 20, 40 and 80 t/ha) and one control (no added prunings) were arranged in a randomized block design with four replicates. Each mixture of prunings and soil was placed in a pot containing 8 kg of soil and maize of Srikandi cultivar was grown on it for 45 days. At harvest, soil pH, P content and aluminium concentration were measured. Results of the glasshouse experiment showed that application of Gliricidia and Tithonia prunings significantly increased soil pH, reduced Alo concentration, increased Alp content, increased P availability, and increased P taken up by maize grown for 45 days. The optimum rate of both Gliricidia and Tithonia pruning should be 40 t/ha. However, at the same rate, optimum production gained by Tithonia would be higher than that of Gliricidia.